Velfærdsstat og to-regimentelære - Petersen, Jørn Henrik (Dansk Teologisk Tidsskrift, 2015)
Primarily based on works by the British archbishop William Temple and the Norwegian bishop Eyvind Berggrav, the article reflects on the relation between the Lutheran doctrine of the two kingdoms and the development of the modern state in general and the welfare state in particular. At the end, the reception among Danish church people of the welfare state and Berggrav’s views is presented.